Joan Robinson and economic theory - ASIMAKOPULOS, A. (PSL Quarterly Review, 2013)
Joan Robinson’s interest in the question of the distribution of income and her disdain for what she considered to be theories that tried to justify existing distributions of income never flagged. Her work is marked by a strong inclination for clear, well reasoned arguments that left no room for sloppy habits of thought. The wide scope and quantity of Robinson’s writings make it difficult to present a critical evaluation of her contributions within the context of even a lengthy paper. The present one concentrates on her writings in five main areas: (i) the economics of imperfect competition; (ii) the theory of employment; (iii) the theory of accumulation in the long run; (iv) the concept of capital and the production function; and (v) the problem of time in economics as reflected in her writings on the theme history versus equilibrium. JEL: B31, E24